Florida's Organo-Auxin Herbicide Rule—2021 - Brett Bultemeier; Jason A. Ferrell; Gregory MacDonald (EDIS)
Organo-auxin (phenoxy) herbicides have found a place in weed control schemes for peanut, corn, small grains, sugarcane, turf, pasture and forage crops, and many other areas. It is the intent of this publication to clarify and disseminate the Florida Organo-Auxin Herbicide Rule to interested growers and applicators. Major revision by B. Bultemeier, J. A. Ferrell, and G. E. MacDonald; 4 pages. https://edis.ifas.ufl.edu/wg051